MEDIA SOSIAL SEBAGAI SARANA DAKWAH: ANALISIS MAKNA PESAN DAKWAH PADA AKUN FACEBOOK YUSUF MANSYUR NETWORK - Nor Latifah (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2019)
Dakwah experienced significantly develop along with the progress of the time. This can be seen from the number of followers, methods, and media used by the dai. Modernization also provides a role for dakwah activities through the provision of various media that can be used as a means of dawah. The use of social media, for example, provides opportunities for effective and efficient dakwah activities compared to the previous era. This study intends to describe the meaning of dakwah messages in uploading the Yusuf Mansyur Network account on Facebook social media through the determination of research objects, research methods, resources, processing, and data analysis. There were 350 uploads on the Yusuf Mansyur Network account. These data were reviewed using three approaches to the meaning study proposed by Alston. The results of this study show that uploads on these accounts can be categorized into Islamic messages in the fields of theology, worship, and morals. Egalitarian social media characters allow direct interaction between the dai and the object of his dakwah. This egalitarian communication character is seen in uploads and responses in the form of comments from followers of the Yusuf Mansyur Network account.